Positioning of the ancestral gastronomy of the Ecuadorian highlands through nostalgia marketing - Villalba Arias, David; Achig Caiza, Miguel; Alvarez Leon, Marco; Haro Sosa, Giovanny (mktDESCUBRE, 2022)
This review article analyzes the gastronomic culture of Ecuador, which makes it unique worldwide. This derives in the ancestral cuisine that is composed of different methods and techniques of ancestral cooking and food preservation. This cuisine is born from festivals and rituals that were presented in the celebration of the country's own meals and performed since ancient times. The purpose of the research is to make known the millenary cuisine and haute cuisine with a fusion of the current cuisine and its different techniques to keep alive the gastronomic history of the country and recover the Ecuadorian flavors through the use of nostalgia marketing. The methodology used in the research is of an explanatory type with a non-experimental qualitative approach. As a main result it was found that Ecuadorians through marketing can recover the history of the country in the different preparations that are made every day in every home in Ecuador, leading to the conclusion that the ancestral cuisine with the correct application of marketing strategies is present and recognized throughout the world.